SEJARAH STUDI ISLAM KLASIK MODERN KONTEMPORER: TOKOH & ALIRAN - Anwar, Kasful; Saidek , Abdul Rahim; Afriyanti, Rita; Fermidera, Icha; Susanto, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines the historical development of Islamic Studies from the classical, modern, to contemporary periods, with a particular focus on the figures and intellectual trends that have shaped the discipline over time. Islamic Studies did not emerge as a static field of knowledge, but rather evolved dynamically in response to social, political, cultural, and intellectual changes within the Muslim world. During the classical period, Islamic Studies were characterized by the formation of core Islamic disciplines such as Qur’anic exegesis, Hadith studies, jurisprudence, and theology, developed through normative and theological approaches by classical Muslim scholars. In the modern period, Islamic Studies experienced significant paradigm shifts as responses to colonialism, modernization, and Western intellectual challenges, giving rise to reformist thinkers who emphasized rational, historical, and contextual approaches. In the contemporary period, Islamic Studies have increasingly adopted multidisciplinary perspectives, incorporating methods from the social sciences and humanities while engaging with global issues such as pluralism, gender, human rights, and democracy. This study employs a library research method using a historical-analytical approach to examine major works and ideas of prominent scholars in Islamic Studies. The findings indicate that the development of Islamic Studies reflects a continuous intellectual effort to interpret and contextualize Islamic teachings in accordance with changing historical realities. This article is expected to contribute to the academic discourse by providing a comprehensive overview of the intellectual map and future direction of Islamic Studies.